Captain Marvel. Vol. 8, The trials - Thompson, Kelly, 1976-; Grönbekk, Torunn (Marvel Worldwide, Inc., 2022)
Captain Marvel no more! After surviving a brutal fight, Carol Danvers deserves a break - and so does her fellow Marvel, Monica Rambeau. But when Carol suddenly goes missing, the newly sentient cosmic entity called Binary must take her place! The mysterious Binary will soon discover that stepping into the shoes of one of Earth's greatest heroes is no easy feat. And as Binary finds herself plunged into a world she barely understands, the questions about exactly who - and what - she is grow ever deeper! And where is Captain Marvel anyway?!